Circadian preference towards morningness is associated with lower slow sleep spindle amplitude and intensity in adolescents. Issue 1 (December 2017) - Merikanto, Ilona; Kuula, Liisa; Makkonen, Tommi; Bódizs, Róbert; Halonen, Risto; Heinonen, Kati; Lahti, Jari; Räikkönen, Katri; Pesonen, Anu-Katriina
Abstract Individual circadian preference types and sleep EEG patterns related to spindle characteristics, have both been associated with similar cognitive and mental health phenotypes. However, no previous study has examined whether sleep spindles would differ by circadian preference. Here, we explore if spindle amplitude, density, duration or intensity differ by circadian preference and whether these associations are moderated by spindle location, frequency, and time distribution across the night. The participants (N = 170, 59% girls; mean age = 16.9, SD = 0.1 years) filled in the shortened 6-item Horne-Östberg Morningness-Eveningness Questionnaire. We performed an overnight sleep EEG at the homes of the participants. In linear mixed model analyses, we found statistically significant lower spindle amplitude and intensity in the morning as compared to intermediate (P < 0.001) and evening preference groups (P < 0.01; P > 0.06 for spindle duration and density). Spindle frequency moderated the associations (P < 0.003 for slow (<13 Hz); P > 0.2 for fast (>13 Hz)). Growth curve analyses revealed a distinct time distribution of spindles across the night by the circadian preference: both spindle amplitude and intensity decreased more towards morning in the morning preference group than in other groups. Our results indicate that circadian preference is not only affecting the sleep timing, but also associates with sleep microstructure regarding sleep spindle phenotypes.